Reliability of mobile application-based cephalometric analysis for chair side evaluation of orthodontic patient in clinical practice - Maruf H Barbhuiya; Piush Kumar; Rachit Thakral; R Krishnapriya; Madhurima Bawa (Wolters Kluwer Medknow Publications, 2021)
OBJECTIVES: The purpose of this study was to evaluate the accuracy and reliability of Mobile Application-Based Software for chair side cephalometric analysis. MATERIALS AND METHOD: Pretreatment lateral cephalograms of 20 patients (10 males and 10 females) were selected randomly and were traced manually and also using Application-based software (One Ceph). 20 angular and three linear parameters were measured both manually and with the software in all the patients. Inter and intra-operator reliability of one ceph was evaluated and the measured parameters were statistically compared with the manual method (Gold Standard). RESULT: The accuracy of angular and linear values was compared for all 23 parameters and our results showed no significant difference in the two methods used for most of the measurements. Three of the measurements [Angle of convexity (N-A; A-Pog); ANB angle; Upper Incisor to NA (Angular)] did show a statistically significant difference though these were clinically irrelevant. CONCLUSION: Application-based cephalometric analysis can be an effective clinical diagnostic tool for chair-side cephalometric evaluation of orthodontic patient.